시진핑 정부의 공동부유 추진 배경 : 중국사회의 경제적 불평등 분석 - 延元鎬; Wonho Yeon (중소연구, 2023)
본 논문은 현 시점에서 시진핑 정부가 공동부유를 적극적으로 제기하게 된 배경이 중국 사회내 경제적 불평등 양상의 심화에 있다는 문제의식을 갖고 작성되었다. 북경대학교 사회과학연구원의 중국가구패널조사(CFPS) 2012년과 2018년 데이터를 바탕으로 경제학적 접근을 통해 중국의 불평등 문제를 보다 객관적으로 이해하고자 한다는 점에서 연구 목적과 방법론에 있어 기존연구와 차별성이 있다. 특히 본 연구는 도농 간, 동서 지역 간, 계층 간 소득 격차와 함께 주관적 격차 인식을 중심으로 중국의 불평등 문제를 분석했다. 분석 결과, 중국인 개인 소득의 가파른 증가는 삶에 대한 전체적인 만족감을 높였지만, 도시와 농촌, 동부연안과 서부내륙, 남성과 여성, 고학력자와 저학력자 사이에 개인소득 불평등은 악화된 것을 알 수 있었다. 이러한 배경에서 시진핑 정부가 2021년 7월 ‘전면적 소강사회’의 달성을 선언한 이후 다음 단계의 핵심과제로 ‘공동부유’를 설정했다고 판단할 수 있다. 그러나 소득 불평등 문제를 주관적 격차 인식의 문제와 결합하여 생각해보면 중국의 문제 해결이 쉽지 않아 보인다. 중국의 경우 불평등 문제를 해결하기 위해서는 상위소득 계층에 집중된 부를 하위소득 계층에 배분해야하는 상황인데 상위소득 그룹인 도시 거주자, 동부연안 거주자, 남성, 고학력자의 경우 삶에 대한 불만족도 또는 상대적 박탈감이 오히려 하위소득 그룹보다 높은 것으로 나타났다. The Xi Jinping government’s current focus on ‘Common Prosperity’ is due to China’s growing economic inequality. This paper uses Peking University Institute of Social Science Survey’s 2012 and 2018 China Household Panel Survey (CFPS) data to objectively understand China's inequality problem. This study examines income discrepancies across rural and urban areas, east and west regions, income classes, and subjective perceptions of inequality in China. The significant rise in Chinese personal income has enhanced life happiness, but income disparity has worsened between urban and rural areas, the east coast and the west interior, men and women, and the highly educated and the less educated. Against this backdrop, after declaring the “Moderately Prosperous Society in All Respects” achieved in July 2021, it is reasonable that the Xi Jinping government has prioritized “Common Prosperity” for the next phase. However, when we combine income inequality with subjective sense of disparity, China's situation seems intractable. Addressing inequality in China requires redistributing wealth from the upper income groups to the lower income groups, but higher income groups - urban residents, east coast residents, males, and highly educated individuals - are less satisfied with their life or have higher levels of subjective deprivation than the lower income groups.